Maternal uniparental disomy 7 in Silver-Russell syndrome. Issue 1 (January 1997) - Preece, M A; Price, S M; Davies, V; Clough, L; Stanier, P; Trembath, R C; Moore, G E
Abstract : Silver-Russell syndrome (SRS) is characterised by intrauterine and postnatal growth failure accompanied by a variable number of dysmorphic features. It is usually sporadic although a few familial cases have been described. In a prospective study of 33 patients with sporadic SRS, we have studied the parent of origin of chromosome 7 using variable number tandem repeat (VNTR) or microsatellite repeat markers and have identified two patients with maternal uniparental disomy of chromosome 7 (mUPD7). In one family, inconsistent inheritance of paternal alleles of markers on chromosomes other than 7 led to their exclusion from further study. The probands were clinically mild and symmetrical, but showed no gross clinical differences from the 30 patients with chromosome 7 derived from both parents.